(3QSGdI aj KhGH GdhVhA hYbGjOgs - (3eLghds ((3eMeO GdegOGhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj ef YdjfG HGdESdGe hHYO agPG HGH aj KhGH GdhVhA hYbGjOg Yf CHj gQjQI QVj Gddg Yfg Yf GdfHj Udi Gddg Ydjg hSde Cfg bGd s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde hde jQi MSGHG hdG YJGHG hdG ghGd hefge ef jNQL hjheQ HMSGHg hjDeQ Hg Edi GdLfI hefge ef jDeQ Hg Edi GdfGQ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdabg GdMfHdjs